2016
DOI: 10.15252/embj.201593673
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of complement activity mediate inhibitory mechanisms through a common C3b‐binding mode

Abstract: Regulators of complement activation (RCA) inhibit complement‐induced immune responses on healthy host tissues. We present crystal structures of human RCA (MCP, DAF, and CR1) and a smallpox virus homolog (SPICE) bound to complement component C3b. Our structural data reveal that up to four consecutive homologous CCP domains (i–iv), responsible for inhibition, bind in the same orientation and extended arrangement at a shared binding platform on C3b. Large sequence variations in CCP domains explain the diverse C3b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
158
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(161 citation statements)
references
References 112 publications
(301 reference statements)
3
158
0
Order By: Relevance
“…Thus, complex formation with the regulator can only occur if the TED-CUB domain pair is in the closed conformation seen in low salt. The Arg 102 -Glu 1032 salt bridge in C3b and the Arg 104 -Glu 1032 salt bridge in C4b help to stabilise this complex [42,43]. The importance of the domains in the modelling fits.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, complex formation with the regulator can only occur if the TED-CUB domain pair is in the closed conformation seen in low salt. The Arg 102 -Glu 1032 salt bridge in C3b and the Arg 104 -Glu 1032 salt bridge in C4b help to stabilise this complex [42,43]. The importance of the domains in the modelling fits.…”
Section: Discussionmentioning
confidence: 96%
“…Crystallographic studies have clarified how five complement regulators bind to active C3b. These C3b complexes include as ligands Factor H short complement regulator domains (SCR) 1/4, membrane cofactor protein (MCP) SCR-3/4, complement receptor type 1 SCR-15/17, decay acceleration factor SCR-2/4 and variola virus SPICE SCR-1/4 [42,43]. All five crystal structures showed that the complexes between C3b and its SCR regulator involve contacts between the MG2 domain in C3b and the first SCR domain of the SCR pair, together with contacts between TED and the second SCR domain of the pair ( Figure 10E).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them consist of highly conservative domains, called short consensus repeats (SCRs), which bind in the same orientation to the same platform on C3b. MCP possess cofactor activity and binds to C3b via SCRs3-4, DAF exhibits decay acceleration properties and binds to C3b via SCRs 2-4, whereas CR1 interacts with C3b through SCRs 15-17 and has both cofactor and decay acceleration activity [22,29,30]. Out of them, unique is CFH, as it inhibits AP both in the fluid phase and on the cell surfaces.…”
Section: The Alternative Pathway Regulating Proteinsmentioning
confidence: 99%
“…The decay acceleration activity of CFH is due to dislocation of Bb protease, occurring as a result of binding between the first two N-terminal SCR of FH and the α'NT, MG2 and MG6-7 domains of C3b [30,33]. The C-terminal end binds to C3b TED domain and polyanions (glycosaminoglycans, GAG) on the cell surfaces [29]. This ability is crucial to distinguish between host and pathogen cells, which typically do not contain GAG on their surfaces.…”
Section: The Alternative Pathway Regulating Proteinsmentioning
confidence: 99%